2021
DOI: 10.1101/2021.12.16.21267932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Single Dose of COVID-19 mRNA Vaccine Induces Airway Immunity in COVID-19 Convalescent Patients

Abstract: BackgroundMucosal antibodies can prevent virus entry and replication in mucosal epithelial cells and hence virus shedding. Preclinical and clinical studies have shown that a parenteral booster injection of a vaccine against a mucosal pathogen promotes stronger mucosal immune responses following prior infection compared to two injections of a parenteral vaccine. We investigated whether this was also the case for a COVID-19 mRNA vaccine.MethodsTwenty-three COVID-19 convalescent patients and 20 SARS-CoV-2-naive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Unaccountably omitted from consideration is the possibility that prior SARS-CoV-2 infection had primed mucosal immune responses that were recalled by the subsequent systemic vaccination, as noted above ( 14 ). Evidence for this is now forthcoming from a report that systemic vaccination (one dose) of previously infected subjects induced the appearance in peripheral blood of IgA anti-spike antibody-secreting cells with mucosal homing potential approximately one week after immunization, as well as IgA antibodies in nasal fluids ( 15 , reviewed by 80 ), in conformity with the known operation of the mucosal immune system ( 81 ). In previously uninfected subjects, IgA antibody-secreting cells of mucosal phenotype were absent from the circulation and nasal IgA antibodies were not induced, even after a second vaccine dose.…”
Section: Mucosal Immunity To Sars-cov-2 and How It Can Act Against Th...mentioning
confidence: 84%
See 1 more Smart Citation
“…Unaccountably omitted from consideration is the possibility that prior SARS-CoV-2 infection had primed mucosal immune responses that were recalled by the subsequent systemic vaccination, as noted above ( 14 ). Evidence for this is now forthcoming from a report that systemic vaccination (one dose) of previously infected subjects induced the appearance in peripheral blood of IgA anti-spike antibody-secreting cells with mucosal homing potential approximately one week after immunization, as well as IgA antibodies in nasal fluids ( 15 , reviewed by 80 ), in conformity with the known operation of the mucosal immune system ( 81 ). In previously uninfected subjects, IgA antibody-secreting cells of mucosal phenotype were absent from the circulation and nasal IgA antibodies were not induced, even after a second vaccine dose.…”
Section: Mucosal Immunity To Sars-cov-2 and How It Can Act Against Th...mentioning
confidence: 84%
“…In contrast, mucosal immunization induces mucosal responses but not parallel systemic immune responses, thereby demonstrating a considerable degree of mutual independence ( 11 13 ). However, antigens previously introduced by a mucosal route can also prime the immune system so that subsequent systemic immunization induces both systemic and mucosal antibody responses ( 14 , 15 ). There are several examples of the effectiveness of systemic immunization of individuals who were previously exposed to a particular antigen at a mucosal surface for the generation of mucosal responses.…”
Section: Separate and Independent: Mucosal And Systemic Immunitymentioning
confidence: 99%
“…10 The sensitivity of the bead-based antibody assays varied by analyte with the lower limit of quantification [LLOQ] for interleukin [IL]-5 being 0.27 pg/mL 41 and the lower limit of detection [LLOD] being 2.0 pg/mL for IL-5. 40 For the serological assays the reported LLODs were in the range 0.44−11.00 binding antibody units (BAU/mL), 42 while for the electro-chemiluminescent assays the reported total protein levels were only in the μg/mL range. 38 To our knowledge, only one LC-MS/MS method related to protein profiling in NLF has been reported in peerreviewed publications to date.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Common methods for mAb bioanalysis in NLF consist of ELISA, 10,35−37 electrochemiluminescence, 38,39 bead-based antibody assays, 40,41 and other commercially available serological assays. 42 Generally, the ELISA assays were semiquantitative, 36,37 intended for research purposes only (with manufacturer reported range of 250− 16,000 pg/mL), 35 or reported standard curve in the ng/mL range (0.195−200 ng/mL). 10 The sensitivity of the bead-based antibody assays varied by analyte with the lower limit of quantification [LLOQ] for interleukin [IL]-5 being 0.27 pg/mL 41 and the lower limit of detection [LLOD] being 2.0 pg/mL for IL-5.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation